Answer & Step-by-step explanation:
(5√2 - 4√3)(5√2 - 4√3)
We can rewrite this equation into a more simpler form.
(5√2 - 4√3)²
Now, we multiply. When multiplying, its important we multiply each term instead of combining them together.
When you multiply a radical by itself, then the base number will be by itself as the product.
So......
(5)² = 25
(4)² = 16
(√2)² = 2
(√3)² = 3
So, now the equation looks like this..
(25 * 2) + (16 * 3)
Multiply the terms.
50 + 48
Add the numbers.
50 + 48 = 98
So, your answer will be answer choice D. The radical in choice D represents the radicals that are in the problem multiplied together.